Mathematical Modeling and Simulation of Microwave Thawing of Large Solid Foods Under Different Operating Conditions - Campañone, Laura Analía (2010)
Microwaves require shorter times to increase foodstuffs temperature when compared to conventional heating methods. However, there are some problems associated to temperature distribution within the products, owing to the preferential absorption of electromagnetic energy by liquid water, caused by differences between its dielectric properties and those of ice (“runaway”). To analyze the behavior of food microwave thawing, a mathematical three-dimensional (3D) model was developed by solving the unsteady-state heat and mass transfer differential equations; this model can be applied to large systems for which Lambert’s law is valid. Thermal, mass transport, and electromagnetic properties varying with temperature were used. The numerical solution was developed using an implicit Crank–Nicolson finite difference method using the classical formulation for one-dimensional (1D) systems and the alternating direction method in two and three dimensions. The model was validated using experimental data from the literature for 1D and two-dimensional conditions and with experiments performed in our laboratory for 3D heat transfer using frozen meat. It was applied to predict temperature and water concentration profiles under different thawing conditions in meat products and to simulate the effect of a fat layer located at the surface of the meat piece on temperature profiles. For different product sizes in rectangular geometry, numerical simulations demonstrated that microwave thawing times were significantly lower in comparison to conventional thawing methods. To prevent overheating during thawing, the combination of continuous microwave power with simultaneous application of air convection and the application of microwave power cycles, using refrigerated air convection with controlled surface temperature, were analyzed.